ANALISIS WAKTU DAN BIAYA PADA PERBAIKAN TRASH SKIMMER BOAT DENGAN METODE TIME-DRIVEN ACTIVITY BASED COSTING DAN TRADITIONAL COSTING - Rizka Ayuananda Putri (2023)
Trash Skimmer Boat specifically for transporting waste in the waters. A ship requires proper maintenance and repair. However, the calculation of ship repair costs makes the company look for ways to make revenue comparable to the services and facilities available. There are various methods used to calculate the total cost required, one of which is the method Time-Driven Activity Based Costing. The most important thing in the calculation method, time equation (estimated processing time) andcapacity cost rate (cost of capacity rates). The results of the calculation of the TDABC Method and MethodsTraditional Costing have different results. For cost calculations using the TDABC method the results are Rp. 1.139.060.328, while the cost calculation method has a result of Rp. 944.907.480. Between the two results have a price comparison of Rp.194.152.848. Method Time-Driven Acitivity Based Costing has a larger calculation results so that the company will get a high selling value of services. In addition, the TDABC method uses a standard time estimate, that is, an estimate of 8 hours as the standard time for workers to do work. With this estimate makes it easier to calculate costs. Traditional methods are based on the details of each unit of goods or only look at the production volume of goods.